Pemanfaatan Teknologi Digital untuk Meningkatkan Keterampilan Kolaborasi dan Komunikasi Siswa Sekolah Dasar - Barokah, Novita; Slamet Untung (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This research is motivated by the challenges of learning in the digital era, which encourage schools to improve 21st century skills which include collaboration and communication skills by utilizing digital technology which will have a major impact on student success. The use of digital technology in learning is currently a major concern at various levels of education, including elementary schools (SD). The aim of the research is to determine the effect of using digital technology, types of effective digital technology media, and challenges in using digital technology to improve collaboration and communication skills for elementary school students. This research is based on literature study, namely a series of activities related to collecting library data, reading and taking notes, and processing research materials. The results of this research show that the use of digital technology has a big influence on improving the collaboration and communication skills of elementary school (SD) students. Types of effective digital technology media include WhatsApp groups, YouTube, TikTok, Google Classroom, Zoom, Google Meet, Canva and Powerpoint. The challenges in using digital technology are limited technological infrastructure, lack of skills and knowledge of teachers, management and maintenance of technology, choosing appropriate technological methods and media, the digital divide, safety for students and teachers, and concerns about disrupting the values ​​of local wisdom.